Lactancia materna en el desarrollo vínculo afectivo de los niños del nivel inicial I del Centro de Educación Inicial “Benjamin Franklin” ciudad de Riobamba, provincia de Chimborazo - Lema Chirau, Sonia Ximena (2023)
The purpose of this research, entitled breastfeeding in the development of the affective relationship between infants, is to determine the relevance that breastfeeding has in the development of stable affective bonds between mother and their children through the collection of information from the infants of the "Benjamín Franklin" Early Childhood Education Center in the city of Riobamba. The direction of this research was based on a mixed and documentary approach of descriptive level through a non-experimental design. Because of this research tematic, the members to be investigated were ten moms from the initial level I of the "Benjamin Franklin" Initial Education Center, to whom an 8-item survey with closed questions was carried out. This study found that lactation promotes interaction between mother and child and that the formation of intercommunication is essential and crucial. In addition, it was found that the development of happiness hormones improves one's physical, cognitive, and emotional well-being. This conclusion emphasizes that the affectionate